2018
DOI: 10.1111/jfpe.12922
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulated ascorbic acid: Development, characterization, and release profile in simulated gastrointestinal fluids

Abstract: The aim of this study was to produce ascorbic acid (AA) microcapsules by complex coacervation, characterize them, and evaluate the release profile in simulated gastrointestinal fluids. The microcapsules were made of gelatin and pectin at concentrations of 1.0, 2.0, and 3.0%. The coacervated microcapsules were assessed for morphology (by optical microscopy and scanning electron microscopy), water activity (Aw), hygroscopicity, solubility, encapsulation efficiency (EE), thermal behavior, and AA release profile. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Antiradical capability commonly reflects the antioxidant ability, and ascorbic acid in foodstuff and bio-systems acts as antioxidant. As the most effective and natural antioxidant with the least side effects, ascorbic acid can inhibit various diseases caused by oxidative stress in the body, such as cancer, cardiovascular disease, aging and cataracts [ 15 ]. Studies have shown that the mortality from these diseases is inversely related to plasma concentration of ascorbic acid [ 19 ].…”
Section: Bioactivity Of Ascorbic Acidmentioning
confidence: 99%
See 4 more Smart Citations
“…Antiradical capability commonly reflects the antioxidant ability, and ascorbic acid in foodstuff and bio-systems acts as antioxidant. As the most effective and natural antioxidant with the least side effects, ascorbic acid can inhibit various diseases caused by oxidative stress in the body, such as cancer, cardiovascular disease, aging and cataracts [ 15 ]. Studies have shown that the mortality from these diseases is inversely related to plasma concentration of ascorbic acid [ 19 ].…”
Section: Bioactivity Of Ascorbic Acidmentioning
confidence: 99%
“…However, the high viscosity of high-concentration polymers limits the granulation by spray-drying. To a certain extent, the loading capacity is related to the wall-to-core ratio and increases with the increase in the coating of wall materials [ 15 ]. Complex coacervation is the phase separation of at least two hydrocolloids from the initial solution, and then the coacervate phase is deposited around the suspended or emulsified bioactive compounds.…”
Section: Strategies For Improving the Encapsulation And Delivery Of Ascorbic Acidmentioning
confidence: 99%
See 3 more Smart Citations